2016
DOI: 10.1016/j.celrep.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Wnt9a Is Required for the Aortic Amplification of Nascent Hematopoietic Stem Cells

Abstract: All mature blood cell types in the adult animal arise from hematopoietic stem and progenitor cells (HSPCs). However, the developmental cues regulating HSPC ontogeny are incompletely understood. In particular, the details surrounding a requirement for Wnt/β-catenin signaling in the development of mature HSPCs are controversial and difficult to consolidate. Using zebrafish, we demonstrate that Wnt signaling is required to direct an amplification of HSPCs in the aorta. Wnt9a is specifically required for this proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 86 publications
2
77
0
Order By: Relevance
“…Our recent work showed that loss of Wnt9a in the somites caused a decrease in HSC number after initiation of emergence with no discernible negative impact on HSC specification (Grainger and Richter et al 2016). This Wnt signal is unrelated to the somitic requirement for wnt16 , as it is temporally distinct and does not impact specification.…”
Section: Zebrafish Hematopoietic Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent work showed that loss of Wnt9a in the somites caused a decrease in HSC number after initiation of emergence with no discernible negative impact on HSC specification (Grainger and Richter et al 2016). This Wnt signal is unrelated to the somitic requirement for wnt16 , as it is temporally distinct and does not impact specification.…”
Section: Zebrafish Hematopoietic Developmentmentioning
confidence: 99%
“…Overexpression of wnt8 , which in this context potently activates the cell fate pathway, caused an increase in HSCs during the emergence window (Goessling et al 2009). Inhibiting the secretion of all Wnt ligands using a chemical inhibitor of Porcupine (Porcn) (Chen et al 2009), an enzyme which is required for the lipid modification and subsequent secretion of Wnts, also caused a loss of HSCs during the emergence window (Biechele et al 2011, Grainger and Richter et al 2016). …”
Section: Zebrafish Hematopoietic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…WNT (Wingless/INT) signaling is a well characterized pathway in regeneration and stem cell formation, but recent work from the Traver and Willert labs has demonstrated a new role for the WNT pathway in HSC migration to secondary sites such as the CHT (Grainger et al 2016). In their study, Grainger and colleagues depicted how early Wnt signals, specifically Wnt9a, from the developing aorta, prior to 20 hpf, are required for HSCs to undergo an expansion event at 31 hpf.…”
Section: 7 Signals That Regulate Cht Engraftmentmentioning
confidence: 99%